A novel magnet polarity identification method for initial position estimation for sensorless IPMSM drive. Issue 4 (23rd May 2014) - Gu, Minglei; Ogasawara, Satoshi; Takemoto, Masatsugu
<x xml:space="preserve">Abstract</x> This paper proposes a novel magnet polarity identification method for initial position estimation during startup for interior permanent magnet synchronous machine (IPMSM) drives. The rotor's initial position estimation is based on magnetic saliency and employs high‐frequency (HF) components of the voltage and current that are excited by the multi space‐vector pulse‐width modulation (MSVPWM) pattern. However, there is a common trouble in the estimation methods based on the magnetic saliency: it is necessary to identify the magnet polarity in order to distinguish the north and south poles since the estimated position angle is a periodic function with π radians. In this paper, a novel inductance estimation method is presented and the magnet polarity is uniquely identified by the relationship between the estimated inductance and the magnetic saturation effect. Experimental results confirm the advantages of the proposed method: it is reliable, accurate, and convenient, and can be done in real time. © 2014 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.